X Distribution of Accidents That Occurred in All Units of Coal Fired Thermal Power Plant by Using HFACS Technique - Ekmekci, Ismail; Ogmen, Akide Cerci (Journal of Strategic Innovation and Sustainability, 2020)
Necessary measures should be taken to ensure that the energy is uninterrupted in coal-fired thermal power plants. For this reason, in the study, 100 accident reports that occurred in 13 units between 2016-2019 at the X coal-fired power plant were analyzed. The causal factors of these accidents were analyzed statistically and classified using the human factor analysis and classification system (HFACS) method. As a result of the study, the accidents that occurred in 13 units were analyzed according to the HFACS category in the tables and it was concluded that most of them were caused by inadequate management.